IMPLEMENTASI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 03 SEJANGAT KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Mariana Mariana; Otang Kurniaman; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by the low learning outcomes IPS students, with an average grade of 65. Among the students who totaled 17 people only 5 students who completed KKM with classical completeness reached 29.41%. This study is a Classroom Action Research (CAR) conducted aims to improve learning outcomes IPS Elementary School fifth grade students 03 Sejangat Bukit Batu subdistrict to implement cooperative learning model type Two Stay Two Stray (TSTS). Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the increase in the number of students who reach the KKM of 5 people (29.41%) on the base score to 12 people (70.58%) in the first cycle and increased to 17 (100%) in the second cycle. This means that the sample classes have been completed in the classical. An increase in the average learning outcomes of a base score is 65 to 74.12 in the first cycle and 86.18 in the second cycle. An increase in the activity of the teacher. At the first meeting of the first cycle of activity percentages of teachers is 58.33%, 70.83% second meeting. While the second cycle the first meeting with the percentage of 87.50%, and the second meeting increased 91.67%. While the student activity also increased that the first meeting of the first cycle of the percentage of student activity is 54.17%, 66.67% second meeting, the first meeting of the second cycle of 79.17% and a second meeting fixed with an average 87.50%. Results of the study in class V SDN 03 Sejangat Bukit Batu subdistrict prove that the implementation of cooperative learning model type Two Stay Two Stray (TSTS) can improve learning outcomes IPS fifth grade students of SDN 03 Sejangat Bukit Batu subdistrict.Keywords: Cooperative type Two Stay Two Stray, learning outcomes IPS